Colon cancer patient with long-term colon stent placement: Case report and literature review - Huang, Qing; Zou, Min-hong; Liang, Wen-long; Wei, Jian-chang; Xie, Jie-feng; Li, Yong-Qiang; Li, Wang-lin; Cao, Jie (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is the third most common cancer and the second leading cause of cancer mortality globally. Large bowel obstruction (occurring in 15-30% of patients with CRCs) accounts for approximately 80% of medical emergencies related to CRC. Currently, there is no standard treatment of this condition. The European Society of Gastrointestinal Endoscopy (ESGE) recommends self-expandable metal stent (SEMS) as a bridge (two weeks) to surgery for left-sided obstructing colon cancer. In the present report, we describe an 81-year-old male with colon cancer who underwent colon stent placement for 32 months, but later underwent radical resection. A follow-up of more than four-months revealed that his condition was normal. The history as well as application and advantages of SEMS are discussed in this report.